The Law Strength Of Under Hand Deed That Has Passed By Notary as an Authentic Deed in the Proof of Civil Case in District Court of Cirebon - Yensih Yensih; Sukarmi Sukarmi; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to determine: 1) The legal force under hand deed that has been approved by Notary as proof of the authentic deed in civil cases in District Court of Cirebon 2) The weakness of the legal strength under hand deed that has been approved by Notary as proof of the authentic deed in civil cases in District Court of CirebonThe approach used in this paper is empirical juridical with the help of primary data or empirical data as the main data. Sources of primary data obtained through interviews, while secondary data obtained rehabilitated and reconstructed by literature. Data analysis techniques with descriptive analysis.The final conclusion is:1.) The legal force under hand deed that has been approved by Notary as proof of the authentic deed in a civil case in court is not the same strength as the authentic deed, but the under hand deed could be evidence in a civil case in court, and the strength of the deed under hand legalized (legalization) Notary Having strength in numbers, the date, and the certainty of the signature of the parties. Under hand deed strength will be strong ruling legalizing if a Notary was brought to trial a witness to the truth of the deed under his hand legalized. 2) The weakness of the under hand deed, and that, if someone in the under hand deed does not admit the truth of the under hand deed strength is lost, but with the legalization of under hand deed can have the strength law even not same as authentic deed which has the perfect law strength.Keywords : Deed under hand; Legalization; and Strength of evidence.